Seizure-induced shoulder dislocations – Case series and review of the literature. (August 2019) - Langenbruch, Lisa; Rickert, Carolin; Gosheger, Georg; Schorn, Dominik; Schliemann, Benedikt; Brix, Tobias; Elger, Christian E.; Meuth, Sven G.; Kovac, Stjepana
Abstract: Purpose: We aimed to identify clinical characteristics of patients with shoulder dislocations caused by an epileptic seizure. Methods: In our retrospective analysis, we identified 15 patients, recorded over an 8-year period, who were diagnosed with shoulder dislocations in the setting of a bilateral tonic-clonic seizure. Results: Patients were almost exclusively male (13/15) and drug-naïve patients suffering their first or second seizure (14/15). Epilepsy was diagnosed in five of these 14 patients after further diagnostic tests, four patients were diagnosed with a provoked or acute symptomatic seizure and five patients with an unprovoked seizure. Treatment with anticonvulsant drugs (AED) was initiated in 10/15 patients after the first seizure, without recommendation for tapering, although long-term treatment was retrospectively judged to be appropriate for only four of those cases. Posterior dislocations – usually rare – were seen in 12/15 patients and often required complex orthopedic interventions. Conclusions: We conclude that in particular posterior shoulder dislocations are often caused by a first seizure and should always raise the suspicion of an epileptic seizure even in the absence of a clear history. AED treatment likely has a protective effect against this type of injury, even if seizure-freedom is not achieved.